Interrogating pregnancy loss : feminist writings on abortion, miscarriage, and stillbirth (Demeter Press, 2017)
Whereas biomedical and feminist literature treat abortion, miscarriage, and stillbirth as differently conceptualized events, this collection explores the connections between these three categories. How have feminist debates and strategies around reproductive choice invigorated the cultural conversation about miscarriage and stillbirth? How can we imagine more nuanced engagements with the spectrum of experiences that are at stake when a pregnancy ends? And how can we effectively create a space where pregnant people contend with the ways that loss makes meaning for those who grieve and/or celebr.